2010
DOI: 10.1016/j.det.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and Migration, the Diverse Functions of the Laminin α3 Subunit

Abstract: The laminins are a secreted family of heterotrimeric molecules essential for basement membrane formation, structure, and function. It is now well established that the alpha3 subunit of laminins-332, -321, and -311 plays an important role in mediating epidermal-dermal integrity and is essential for the skin to withstand mechanical stresses. These laminins also regulate cell migration and mechanosignal transduction. This article provides an overview of the gene, transcripts, and protein structures of laminin alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…The molecule increases its adhesive activity upon cleavage of the α3 subunit into a 160 kDa isoform [33]. This mature form of LN332 supports the formation of hemidesmosomes, linking the ECM with the keratin cytoskeleton via the integrin α6β4 [3436]. The mature LN332 can also support the formation of focal adhesions by binding to the integrin α3β1, which links the ECM to the actin cytoskeleton [37].…”
Section: Discussionmentioning
confidence: 99%
“…The molecule increases its adhesive activity upon cleavage of the α3 subunit into a 160 kDa isoform [33]. This mature form of LN332 supports the formation of hemidesmosomes, linking the ECM with the keratin cytoskeleton via the integrin α6β4 [3436]. The mature LN332 can also support the formation of focal adhesions by binding to the integrin α3β1, which links the ECM to the actin cytoskeleton [37].…”
Section: Discussionmentioning
confidence: 99%
“…A good example of this is a rare disorder termed laryngo-onycho-cutaneous syndrome (LOC) which presents with non-healing cutaneous erosions and chronic overproduction of granulation tissue without apparent skin fragility [27]. Mutational analyses have revealed that LOC syndrome results from mutations in the first exon of the laminin α3a transcript implicating this region in the regulation of the granulation tissue response [27]. …”
Section: Skin Diseases Involving Hemidesmosomes and Focal Contactsmentioning
confidence: 99%
“…These changes disrupted the formation and maturation of desmosome junctions. We hypothesized that the global change in RhoA activity may also affect cell–substrate attachments, including integrin-based focal adhesions, as such adhesions are known to regulate cell behavior via functional interactions with small GTPases and the actin cytoskeleton (Hamill et al, 2009; Hamill et al, 2010; Hamill et al, 2011; Tsuruta et al, 2011; Hong et al, 2012). We set out to address the possibility that PKP2 functions to integrate signals within the keratinocyte adhesive network of both cadherin- and integrin-based adhesions.…”
Section: Introductionmentioning
confidence: 99%